THE BRONZE AXE FROM MIHALŢ (ROMANIA) AND SOME PROBLEMS RELATED TO HYBRID “LARGA” TYPE AXES - Cristian Ioan POPA (Journal of Ancient History and Archaeology)
Along with the well-known metal artefacts produced in series specific to the Bronze Age, unique, prestige products were also manufactured in the Carpathian area. Among them the Larga type axes stand out both by their very small number and by their beauty. Summing up specific elements, found individually and in the case of other axes (semi-calotte flat, curved blade, decoration on the sleeve and so on), the use of the term hybrid axes is justified. Their similarity with Drajna-type axes is obvious, supporting their symbolic value. The last known axe, discovered in Mihalţ, in a gravel pit, is also the only Transylvanian piece, the rest of the discoveries being known from Maramureş and Ukraine. Their dating is relative, with no specific context, but they can be dated in the Late Bronze and associated / contemporary with Wietenberg, Gligoreşti or Komarow manifestations.